Rubén Darío. Despedidas de la Tierra - Medina, Julia M. (2019)
In looking at different genres, this article addresses some of Rubén Darío’s lasts texts, to illustrate how his work disavows modernity as understood and practiced traditionally, even by him; thereby suturing unconsolidated spheres of a world still fragmented.